Credit, Securitization and Monetary Policy : Watch Out for Unintended Consequences - Pescatori, Andrea (IMF Working Papers; Working Paper ;, 2016)
We show evidence that interest rate hikes slowdown loan growth but lead intermediation to migrate from banks' balance sheets to non-banks via increased securitization activity. As such, higher interest rates have the potential for unintended consequences; raising systemic risk rather than lowering it by pushing more intermediation activity to more weakly regulated sectors. In the past, this increased securitization activity was driven primarily byb private-label securitization. On the other hand, the government sponsored entities like Freddie Mac and Fannie Mae appear to react to higher policy rates by cutting back on their securitization activity but expanding loans to the Federal Home Loan Bank system.